Impact of Low-Intensity Hunting on Game Species in and Around the Kanuku Mountains Protected Area, Guyana - Hallett, Matthew T.; Kinahan, Anouska A.; McGregor, Rayon; Baggallay, Thadaigh; Babb, Timothy; Barnabus, Howard; Wilson, Asaph; Li, Fernando M.; Boone, Wesley W.; Bankovich, Brittany A. (Frontiers in Ecology and Evolution, 2019)
Unsustainable harvest is driving population declines in tropical forest species across the globe. Despite maintaining the second highest percent forest cover in the world (85%), concern is increasing in Guyana that unmanaged commercial and subsistence hunting activities could result in defaunation, and the cascading ecological effects of ‘empty forests.’ The Rupununi region in southwestern Guyana, home to the Kanuku Mountains Protected Area (KMPA), hosts one of the world’s lowest human population densities (0.42 people/km2), as well as large tracts of both Neotropical savanna and forest habitats, making it one of the country’s most biodiverse regions. Indigenous Makushi and Wapichan communities that reside there have maintained subsistence lifestyles mediated by traditional beliefs and management practices for millennia. However, as human populations and access to markets increase, there is a corresponding increase in harvesting of natural resources. Protected areas have long been recognized for their role in biodiversity conservation, while also serving as a reserve for subsistence hunters. The KMPA, one of Guyana’s newest protected areas, allows for the continued sustainable use of its resources by indigenous communities. It is critical to understand the patterns, impacts, and sustainable levels of hunting in and around the protected area so that biodiversity can be managed and conserved effectively. Our study shows that the impact of current hunting intensity in and around the KMPA remains relatively low and supports the hypothesis that Neotropical forests can support hunting pressure of <1 person/km2. While our results show that current levels of hunting in the region can be considered sustainable, small shifts in activity patterns and relative abundance of preferred game species were observed in higher intensity hunting areas, which in turn appeared to have influenced other non-hunted species’ activity patterns and relative abundance. Our results suggest therefore, that even in low hunting intensity areas, monitoring both preferred game and non-hunted species’ activity patterns and abundances is important to act as an early warning system before animal populations are significantly impacted by overharvesting. Further, our study highlights the importance of considering the entire ecosystem and not simply individual populations when establishing sustainable harvesting rates for an area.